Genome Sequence of a Natural Reassortant H5N2 Avian Influenza Virus from Domestic Mallard Ducks in Eastern China - Gu, Min (American Society for Microbiology, 2012)
Here, we report the genomic sequence of a Chinese reassortant H5N2 avian influenza virus which possessed the polybasic motif PLREKRRK-R/GL at the hemagglutinin cleavage site. Phylogenetic analysis showed that all eight genes were of the Eurasian lineage, five of which were highly homologous to the endemic clade 2.3.4 H5N1 viruses and their H5N5 reassortant descendants. These data suggested that novel multisubtypic NA reassortants bearing the H5N1 backbone could be generated through genetic reassortment in H5N1 circulating regions, which will help in understanding the evolution and segment reassortment mechanism of H5 subtype avian influenza viruses.